Concurrence par comparaison et transformations quasi-marchandes - Pierre-André Juven (Revue de la Régulation)
By implementing cost accounting in the 1980 and a prospective payment system in the 2000, french reformers of hospitals have explicitely tried to put into practice the idea of yardstick competition. This paper show how the ministry of health has tried to embody this quasi-market transformation within devices such as cost accounting and pricing process and why this yardstick competition articulates a market principle and a technocratic conception of regulation. The implementation of this yardstick competition implies a commensuration process of the public and the private sector which reveals some limits of this model.